2014
DOI: 10.1136/bcr-2013-202908
|View full text |Cite
|
Sign up to set email alerts
|

An infant with chronic severe neutropenia

Abstract: Neutropenia in infancy and childhood poses a diagnostic challenge as the aetiology ranges from acute life-threatening conditions to chronic benign diseases. Chronic benign neutropenia of infancy is a rare disorder occurring in 1:100,000. The neutrophil count continues to be low for a prolonged period until spontaneous resolution by the age of 3-4 years. Such infants are having higher incidences of minor infections requiring treatment with antibiotics and rare incidences of meningitis and sepsis. The authors de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 5 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Chronic idiopathic neutropenia has been reported to have a relatively mild prognosis [ 2 , 4 , 17 , 26 , 32 ]. However, neutropenia progress to severe forms such as hematologic malignancy in congenital neutropenia [ 1 , 6 , 33 , 34 , 35 , 36 ]. This study shows that severely low levels of neutrophil count during a long-term period do not necessarily lead to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic idiopathic neutropenia has been reported to have a relatively mild prognosis [ 2 , 4 , 17 , 26 , 32 ]. However, neutropenia progress to severe forms such as hematologic malignancy in congenital neutropenia [ 1 , 6 , 33 , 34 , 35 , 36 ]. This study shows that severely low levels of neutrophil count during a long-term period do not necessarily lead to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The ANC can be highly variable in CBN typically ranging from 0 to 500 with fluctuations occurring irregularly. 3 While autoantibodies have been detected, they are not always present. 6,7 One study found them only in 21% of patients diagnosed with CBN.…”
Section: Discussionmentioning
confidence: 99%
“…15 Thankfully, this condition is largely self-limited in infancy with 95% achieving remission within 3 years. 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment is generally supportive in nature. Despite the low ANC, the risk of infection is not high 38,39 …”
Section: Neutropenia With Normal Marrow Reservementioning
confidence: 99%